Studi Perilaku Balok Beton dengan Tulangan Bambu Laminasi Limbah Plastik - Bastian Artanto Ampangallo (Journal on Education, 2022)
The method used in this study is an experimental method by conducting a series of tests ranging from bamboo preservation, bamboo lamination and aggregate testing. The design of concrete mix design uses the SK SNI 03-2834 - 2000 method. The dimensions of the beam used are 900 mm long, 100 mm wide, and 150 mm high. Variations in the shape of the bamboo reinforcement used are square and circle diameter of 10 mm.The results showed that the flexural strength produced by steel reinforcing concrete blocks was 842.4253 Kgm, square laminated bamboo reinforcement concrete blocks amounted to 546.7123 Kgm, and circular laminated bamboo reinforcement concrete blocks amounted to 536.5153 Kgm. The percentage of average flexural strength of laminated bamboo reinforcement is equivalent to 60% of steel reinforcement.